The Approach of Schools to Ethnic Diversity: The Perspective of Majority and Minority Pupils - Karmen Mlinar; Mojca Peček (Center for Educational Policy Studies Journal)
The growing multiculturalism in schools in most European countries, including Slovenia, poses new challenges for both teachers and pupils. Although the Slovenian school system relies on numerous strategies and guidelines for the inclusion of minority pupils, discrimination is still an everyday issue, especially when it comes to pupils from former Yugoslav countries and Roma. The aim of the present study was to investigate how pupils (N = 897) from minority groups (Albanians, Bosniaks, Hungarians, Roma, Serbs) perceive the approach of schools to ethnic diversity in comparison to the majority group (Slovenians). Exploratory factor analysis was conducted on a self-developed scale, resulting in a twofactor solution: schools’ efforts to embrace distributive equality (F1) and to foster diversity recognition (F2). For each factor, the perceptions of minorities were compared with those of the majority. The results show statistically significant differences in the perceptions of Bosniaks and Slovenians within F1, and of Hungarians and Serbs and Slovenians within F2. Furthermore, an analysis of the differences in the perception of F1 and F2 for each ethnic group show statistically significant differences for all ethnic groups except for Hungarians. The results suggest that the Slovenian school system needs to re-evaluate its practices by making more effort to foster the recognition of diversity. By recognising and valuing diversity alongside equality, schools can better address discriminatory practices and promote inclusion, which leads to the uniqueness of each identity being respected, valued and appreciated. Possible strategies to achieve this goal are discussed.